THEORETICAL CONCLAVE: ARE SALES VISIONARIES SHAPING TOMORROW'S SALES LANDSCAPE? - Chee, How Liau (INTI International University, 2023)
This article delves into an analysis of motivation theories within the context of personal selling, exploring their implications for the development and optimization of salesperson compensation plans. The initial section reviews prominent motivation theories, offering insights into their principles and applications. Subsequently, the article transitions to a discussion on the practical utilization of these theories in the design and implementation of compensation structures for sales professionals. By examining the intersection of motivation theories and salesperson compensation, this article aims to contribute valuable perspectives to the ongoing discourse in sales management and organizational behavior. The findings presented herein offer a nuanced understanding of how motivational factors can be strategically harnessed to enhance sales performance and align with broader organizational objectives.